UPAYA PENERAPAN METODE COOPERATIVE LEARNING TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN MEMBACA BAHASA INGGRIS SISWA - Muhtasim Muhtasim (Jurnal Paedagogy, 2015)
The purpose of this study was to determine the process of using the Cooperative Learning Type Group Investigation method to improve reading skills and learning outcomes of English subjects in Class XI-IBB-2 SMA Negeri 1 Praya Timur. The research method used is classroom action research. The subjects of this study were 30 students consisting of 14 male students and 16 female students. The research data collection instruments used tests, observation sheets, and documentation. This research data analysis technique using qualitative and quantitative descriptive analysis. The results of this study indicate that reading skills (reading skills) in English using the Group Investigation Type method can improve student learning outcomes of Class XI-IBB-2 SMA Negeri 1 Praya Timur. This increase can be seen from the classical completeness obtained in the first cycle of 63.33% and the second cycle increased to 90.00%, an increase of 26.67%. This increase can also be seen from the results of observations of teacher activity by 12 in the good category in cycle I and increasing to 17 in the very good category in cycle II. Meanwhile, student activity in the first cycle was 42 in the active category, increasing to 65 in the very active category in the second cycle. Based on the results of the analysis of cycle I and II, it was obtained an increase in classical completeness by 26.67%.